2010
DOI: 10.1186/1744-8069-6-54
|View full text |Cite
|
Sign up to set email alerts
|

Injury Induced Activation of Extracellular Signal-Regulated Kinase (ERK) in the Rat Rostral Ventromedial Medulla (RVM) is Age Dependant and Requires the Lamina I Projection Pathway

Abstract: Descending controls originating in part from the rostral ventromedial medulla (RVM) regulate the excitability of dorsal horn neurons and maintain peripheral pain states. Activation of extracellular signal regulated kinase (ERK) in RVM neurons has been shown following peripheral inflammation and is involved in generating the accompanying inflammatory hyperalgesia. Here, we show that spared nerve injury (SNI), a model of neuropathic pain, results in an increase in ERK activity in RVM neurons of adult rats 3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The involvement of pERK1/2 in the maintenance of chronic neuropathic pain is well established (Geranton, Tochiki, Chiu, Stuart, & Hunt, ; Ma & Quirion, ; Song et al, ). SNI animals receiving amylin chronically presented a significantly higher number of pERK1/2‐positive cells than both SHAM groups, suggesting amylin may trigger the ERK1/2 cascade under neuropathic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of pERK1/2 in the maintenance of chronic neuropathic pain is well established (Geranton, Tochiki, Chiu, Stuart, & Hunt, ; Ma & Quirion, ; Song et al, ). SNI animals receiving amylin chronically presented a significantly higher number of pERK1/2‐positive cells than both SHAM groups, suggesting amylin may trigger the ERK1/2 cascade under neuropathic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the brainstem raphe sub‐nuclei, the chronic constriction injury was associated with increased pERK expression. Increased pERK in the raphe magnus is also reported following spared nerve injury, which has been shown very convincingly to contribute to the increased sensitivity to mechanical stimuli and to depend on lamina I and II inputs (Geranton et al., ). The expression of pERK1/2 was selectively decreased in the raphe obscurus by acute noxious stimulation in rats with mononeuropathy, which stood in contrast to their non‐neuropathic counterparts in which it was increased.…”
mentioning
confidence: 92%
“…Depletion of the spinal serotonin reduced the activation of the ERK evoked by the formalin. It has also been demonstrated that the ERK is activated in the RVM following peripheral inflammation or injury, and much of the ERK activation has been found in the serotonergic neurons [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%